Microalgae-integrated building enclosures: a nature-based solution for carbon sequestration - Kim, Kyoung Hee; Parrow, Matthew W.; Kheirkhah Sangdeh, Parham (Frontiers in Built Environment, 2025)
The rapid urbanization, population growth, and technological advancement have exacerbated global warming and environmental impacts. Buildings are one of the primary contributors to anthropogenic pollution and climate change. While net-zero energy buildings powered by renewable energy systems can help alleviate carbon emissions, a major challenge remains in addressing embodied carbon throughout the entire life cycle of buildings, including material processing, manufacturing, construction, and end-of-life phases. Therefore, it is important to implement carbon removal strategies in buildings and cities. Carbon removal strategies primarily include two categories: nature-based solutions such as reforestation, wetland restoration, and blue carbon strategies and technology-based carbon removal such as carbon capture and storage and direct air capture. This paper outlines nature-based solutions suitable for a built environment while still actively improving additional environmental benefits such as human wellbeing and overall ecosystem health. In particular, the research focuses on multifunctional microalgae-integrated building enclosures for efficient carbon sequestration. Due to their strong photosynthetic capability and rapid growth, microalgae have received significant attention for their carbon capture potential. Photobioreactors fabricated into buildings and industrial infrastructure allow microalgae to sequester more carbon while simultaneously producing biomass feedstock and other valuable biomass commodities. This study tested a microalgae photobioreactor-integrated window system using Chlorella and Chlorococcum. Our results indicated that Chlorella’s daily yield in a microalgae window was 175 mg/L-day, while Chlorococcum’s daily yield was 80 mg/L-day, which are consistent with the data published in the literature. These results demonstrate the viability of microalgae building enclosures for real-world carbon capture. The research suggests that a range of microalgae strains coupled with well-controlled growing environments has potential for cost-effective large scale carbon sequestration in the built environment; however, the combination of regulating ideal growing environmental conditions with the building energy efficiency of the microalgae enclosure system are areas of future research. Algal carbon sequestration, when combined with net-zero buildings, can address global warming and help sustainable urban development.